Optimalisasi Pemasaran Online Bagi UMKM melalui Strategi Digital Branding dan SEO - Nadi, Luh; Wenten, I Ketut; Gunarto, Rudy Irawan (Universitas Pamulang, 2025)
Amidst the rapid digital transformation, Micro, Small, and Medium Enterprises (MSMEs) face major challenges in reaching the digital market effectively. Lack of understanding of digital branding and Search Engine Optimization (SEO) strategies causes the visibility of MSME products in the online realm to be still low, thus hampering the growth and competitiveness of their business. For that, we, the lecturers, want to carry out Community Service at the Cibadung Village office, Gunung Sindur sub-district, Bogor Regency. This Community Service aims to help and provide direction and input for MSMEs in Cibadung Village in solving problems faced by digital marketing activities, to optimize MSME online marketing through increasing competence in building a digital brand image and implementing SEO techniques practically and sustainably. This Community Service is carried out using lecture, tutorial, discussion and evaluation methods. This Community Service was attended by 45 MSMEs. MSMEs are given an understanding of the importance of building a strong brand image (Branding) and increasing digital traffic through basic SEO techniques. After the presentation of the material, these MSMEs were free to ask questions as widely as possible to the speakers, and there were many questions from the participants regarding the presentation of the material. As a result, the activity showed that participants experienced asignificant increase in their ability to manage digital media, build a strong brand image, and increase digital traffic through basic SEO techniques. Keywords: UMKM, Digital Branding, SEO, Online Marketing, Digital Visibility